Analisis Pengaruh Karakteristik Individu terhadap Pengembangan Karier Karyawan pada Sekolah Tinggi Agama Islam Negeri Jember: Analysis of the Influence of Individual Characteristics on Employee Career Development at the State Islamic Institute of Jember - Abdul Rahim (Fenomena, 2008)
The phenomenon of bureaucratic rigidity and the use of seniority as the primary basis for career advancement often creates stagnation for competent employees in government institutions, including STAIN Jember. This issue is critical because without a merit-based system, organizational competitiveness and employee motivation decline. Grounded in human resource management theory, this study addresses how individual characteristics influence career development. The research aims to analyze the partial and simultaneous effects of expertise, education level, and work experience on employee career development. A quantitative approach was employed using multiple linear regression analysis, with data collected from 33 employees through questionnaires, interviews, and documentation. The findings reveal that simultaneously, all three variables significantly affect career development, contributing 64.8%, while the remaining 35.2% is influenced by other factors. Partially, education level and work experience have significant positive effects, whereas expertise does not show a significant individual effect. Education level emerges as the most dominant factor. The study concludes that career development policies in government institutions must prioritize formal education and work experience, while expertise needs to be better integrated into promotion systems. It is recommended that STAIN Jember revise its career planning regulations to be more competency-based. Fenomena kekakuan birokrasi dan penggunaan senioritas sebagai dasar utama kenaikan jabatan sering menciptakan stagnasi bagi pegawai kompeten di instansi pemerintah, termasuk STAIN Jember. Isu ini krusial karena tanpa sistem berbasis merit, daya saing organisasi dan motivasi pegawai menurun. Berlandaskan teori manajemen sumber daya manusia, penelitian ini mengatasi bagaimana karakteristik individu mempengaruhi pengembangan karier. Penelitian ini bertujuan menganalisis pengaruh parsial dan simultan keahlian, tingkat pendidikan, dan pengalaman kerja terhadap pengembangan karier pegawai. Pendekatan kuantitatif digunakan dengan analisis regresi linier berganda, data dikumpulkan dari 33 pegawai melalui kuesioner, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa secara simultan ketiga variabel berpengaruh signifikan terhadap pengembangan karier, memberikan kontribusi sebesar 64,8%, sementara sisanya 35,2% dipengaruhi faktor lain. Secara parsial, tingkat pendidikan dan pengalaman kerja memiliki pengaruh positif signifikan, sedangkan keahlian tidak menunjukkan pengaruh signifikan secara individu. Tingkat pendidikan menjadi faktor paling dominan. Kesimpulannya, kebijakan pengembangan karier di instansi pemerintah harus memprioritaskan pendidikan formal dan pengalaman kerja, sementara keahlian perlu diintegrasikan lebih baik dalam sistem promosi. Direkomendasikan agar STAIN Jember merevisi peraturan perencanaan kariernya agar lebih berbasis kompetensi.